1984
DOI: 10.1002/pen.760241706
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization of polyester/polyamide blends via catalytic ester‐amide interchange reaction

Abstract: In a series of publications we reported on melt rheology, morphology, and mechanical properties of the poly(ethylene terephthalate)/poly(amide‐6,6) blends (PET/PA). The non‐oriented samples had poor interphase bonding resulting in low impact and tensile strengths. To improve these properties the ester‐amide interchange reaction was carried out in solution and in melt. In the latter case a Brabender Plastograph was used in the mixing chamber or twin‐screw extruder configurations with p‐toluenesulfonic acid as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
4

Year Published

1989
1989
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(89 citation statements)
references
References 21 publications
1
83
0
4
Order By: Relevance
“…[114] Transamidation reactions between two PAs have been studied by, for example, Kricheldorf, [115,116] whereas Kotliar [117] has written an excellent general review paper on interchange reactions involving condensation polymers. The work by Pillon and Utracki [118,119] nicely demonstrates the efficiency of compatibilization by (limited) interchange reactions. Equimolar blends of PET and PA 6.6 were prepared in a twin screw extruder.…”
Section: Compatibilization Via Interchange Reactionsmentioning
confidence: 88%
“…[114] Transamidation reactions between two PAs have been studied by, for example, Kricheldorf, [115,116] whereas Kotliar [117] has written an excellent general review paper on interchange reactions involving condensation polymers. The work by Pillon and Utracki [118,119] nicely demonstrates the efficiency of compatibilization by (limited) interchange reactions. Equimolar blends of PET and PA 6.6 were prepared in a twin screw extruder.…”
Section: Compatibilization Via Interchange Reactionsmentioning
confidence: 88%
“…This indicates that polyester-polyamide copolymers are formed through an ester-amide interchange reaction during the melt blending of polyester and polyamide [32]. Other authors [33,34] have characterized the ester-amide interchange reaction of polyethylene terephthalate (PET) and polyamide (PA) catalyzed by p-toluenesulfonic acid using DSC, 1H…”
Section: Thermal Analysis Of the Reinforcing Fibrementioning
confidence: 99%
“…When blending a poly-(ether ester) with the nylon, an ester-amide interchange reaction may occur. Pillon, Utracki et al 29'3° demonstrated experimentally the occurrence of this reaction in the blending process of poly(ethylene terephthalate) and polyamide-6,6. Since blends M8 to M11 scored postively in the Molau test and considering the small average the blends are plotted against the weight-average particle sizes in order to avoid this problem.…”
Section: Influence Of Rubber Propertiesmentioning
confidence: 99%